Scientific production of nursing about pre-hospital service and first aid: study trends (Research, Society and Development, 2022)
This article aims to analyze the trends of Brazilian scientific nursing productions regarding pre-hospital care and first aid. It is a narrative review of literature, developed through access to the research available in the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel. The systematic search for studies was carried out in June 2020, with the strategies "pre-hospital care" AND "Nursing", resulting in 90 records and "first aid" AND "Nursing", resulting in 24 records, totaling 114 records. 66 studies were selected and analyzed as determined by Brum et al. (2016). The data were organized into the thematic categories: characterization of the analyzed studies; pre-hospital care and mobile emergency care; pre-hospital care in nursing care; worker health and pre-hospital care; first aid education and pre-hospital care; technologies in first aid and pre-hospital care; and nursing management in pre-hospital care. It is considered that the trend of Brazilian scientific production generally relates pre-hospital care and first aid to nursing care, especially assistance in the mobile emergency care service, and that the topic has been little explored in relation to training. of nurses, highlighting the need to pay attention to the development of this stage of academic training.